The effect of moisture content in the production of agarwood tea: article / Izni Syazana Ismail and Habsah Alwi - Ismail, Izni Syazana; Alwi, Habsah (2019)
Tea is a beverage that consume by people the most, aside water. Agarwood tea has so many benefits such as the antioxidant activities, anti-hypertensive and anti-inflammatory. A few benefits have been proven by a study on the Agarwood tea. The process of making Agarwood tea is the same as the process of making green tea from the leaves of Camellia sinensis. In this study, the equipment used for the drying process was Vacuum Far-Infrared Radiation (VFIR) dryer and the leaves used were Aquilaria Subintegra species. Based on the previous research, the optimum parameters of the VFIR dyer were set at 50˚C and 0.6 bar for 120 minutes for drying to study the chemical constituents in the Agarwood leaves. However, since previous study just used constant drying period, thus in this research, the first experiment conducted used the same parameters but only varying the time in order to find the optimum drying period. As for the result, 120 minutes is the optimum drying period after studying the moisture content removal analysis, colony count analysis and antioxidant activity. Another experiment conducted to study on the how moisture content of different storage conditions affects the lifespan of Agarwood tea. The two storage conditions used were the kitchen and air-conditioning room. The results of the samples were obtained every 7 days which repeated for 28 days by studying the moisture content removal analysis, colony count analysis and antioxidant activity. This study shows that the Agarwood tea stored in the air-conditioning room was actually increase its lifespan as long the tea was kept in a sealed packaging.